Molecular detection of toxic pseudo-nitzschia species (Bacillariophyceae) by whole-cell fluorescene in situ hybridization - Suk Hui, Voon (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Some species in the genus Pseudo-nitzschia have the ability to produce domoic acid (DA). DA is a potent neurotoxin responsible for a human intoxication known as amnesic shellfish poisoning (ASP). Identification of the species mainly depends on the morphological observation which is insufficient to discriminate to the species level. Species identification of Pseudo-nitzschia acquires application of inclusive electron microscopy to investigate the fine ultrastructures of frustules. In this study, a molecular approach was applied to identify the harmful Pseudo-nitzschia species by using the whole-cell fluorescence in situ hybridization (FISH). The rRNA-targeted oligonucleotide probes were successfully designed in silico targeting P. pungens, P. brasilina and P. caciantha. The P. pungens species-specific probe was tested using Pseudo-nitzschia culture samples. The results showed high specificity and accessibility of the probe. The probe was further tested on natural seawater samples with cell spiking. Our results indicated that the fluorescent oligonucleotide probes (PuD1) show great promise as a tool that can facilitate the detection of P. pungens in the phytoplankton samples. The whole-cell FISH method was proven as a rapid detection tool for Pseudonitzschia with high specificity. This approach is suggested to be adopted in the country harmful algae monitoring and mitigation.